The production and characterization of fluoroquinolone amorphous solid dispersions - MESALLATI, HANAH NADINE (Trinity College Dublin. School of Pharmacy & Pharma. Sciences. Discipline of Pharmacy, 2017)
Ciprofloxacin (CIP) is a Biopharmaceutics Classification System class 4 drug, which exhibits solid-state limited solubility. Among the different formulation options available to improve the solubility of such a compound, amorphization provides a number of advantages. However, unlike many other poorly soluble drugs, little research has been conducted on CIP in this regard. The primary aim of this project was therefore to produce stable amorphous formulations of this drug, in order to improve its pharmaceutical properties. For the first time, the production of pure amorphous CIP was achieved by spray drying a dilute solution of the drug in pure water. It was discovered that the most stable form of anhydrous CIP is the zwitterion, however it converts to the unionized form when heated to its melting point. The reverse reaction then occurs when unionized CIP is exposed to high humidity. In order to reduce the crystallization tendency of amorphous CIP, its formulation as an amorphous solid dispersion (ASD) was required. The suitability of a number of polymers and small molecules as stabilizers for CIP was examined. Fully X-ray amorphous solid dispersions were only obtained when CIP was ball milled with acidic polymers such as Eudragit L100, Eudragit L100-55, Carbopol and HPMCAS. An ionic interaction was detected between the piperazine amino group of CIP and carboxylate of the polymer in each ASD. The strength of these drug-polymer interactions contributed to the higher than expected glass transition temperatures (Tgs) of the samples, and rendered them resistant to crystallization during thermal and water sorption studies. Polymer/salt ASDs consisting of amorphous CIP/succinic acid salts dispersed in PVP or Soluplus were found to be less stable, and crystallized during these analyses. Similar results were obtained with ASDs containing CIP and various amino acids. Evidence of salt formation was also found in the latter samples via FTIR and solid-state nuclear magnetic resonance analysis, in this case between the protonated secondary amine of the drug and the carboxylate groups of aspartic acid, glutamic acid, cysteine and arginine. All of the ASDs produced in this project were more soluble than crystalline CIP in water and biorelevant media. A much greater increase in solubility was obtained with the ASDs containing more acidic stabilizers, such as succinic, glutamic and aspartic acid. However, the effective permeability of these samples was found to be lower than that of CIP. In contrast, the ASDs containing cysteine, arginine and HPMCAS demonstrated higher effective permeability than the pure drug, while no decrease was seen with the other binary polymeric ASDs. For comparison, enrofloxacin (ENRO), a close analogue of CIP that bears an ethyl substituent on its piperazine ring, was subjected to a number of the same investigations as CIP. ENRO showed the same affinity as CIP for polymers, and its piperazine amino group also appears to be protonated in the successful ASDs, forming an ionic bond with the carboxylate groups of the polymers. The stability of the ASDs was reflected in their elevated Tgs and lack of crystallization during water sorption studies. They also reached higher drug concentrations during solubility and dissolution studies than the pure drug. Like the corresponding polymeric CIP ASDs, no decrease in antibiotic efficacy was observed with the ENRO ASDs, while significant improvements were obtained with the ASDs containing HPMCAS. Due to the lack of comprehensive studies examining CIP or ENRO ASDs, this work adds substantially to the body of knowledge concerning the amorphous form of these poor glass-forming drugs. While all of the ASDs significantly increased the solubility of CIP, the binary polymeric ASDs offered a more favorable solubility-permeability balance, and were also more stable than the amorphous salts containing succinic acid or amino acids. Therefore, they may be a viable formulation option for improving the bioavailability of CIP.
APPROVED
Keywords: Ciprofloxacin; Amorphous solid dispersion; Solubility; Permeability